2020
DOI: 10.1371/journal.pone.0227740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epoch length on intensity classification and on accuracy of measurement under controlled conditions on treadmill: Towards a better understanding of accelerometer measurement

Abstract: The aim of this study was to analyze the effect of epoch length on intensity classification during continuous and intermittent activities. Methods Ten active students exercised under controlled conditions on a treadmill for four 5-min bouts by combining two effort intensities (running and walking) and two physical activity (PA) patterns (continuous or intermittent). The testing session was designed to generate a known level of moderate to vigorous PA (MVPA) for each condition. These PA levels were used as crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Our results showed that both the number of epochs and the learning rate (LR) exhibited significant effects on the testing accuracy (p < 0.05), and when the number of epochs was 30 and the LR was 0.001, the model achieved an accuracy of 98.06 ± 1.02%. The number of epochs was the number of times that the entire training dataset was used for the algorithm learning process, and each epoch consisted of one or more batches that were used to tune the internal model parameter 26 . Theoretically, more epochs should result in higher accuracy 27 , although a longer runtime was required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that both the number of epochs and the learning rate (LR) exhibited significant effects on the testing accuracy (p < 0.05), and when the number of epochs was 30 and the LR was 0.001, the model achieved an accuracy of 98.06 ± 1.02%. The number of epochs was the number of times that the entire training dataset was used for the algorithm learning process, and each epoch consisted of one or more batches that were used to tune the internal model parameter 26 . Theoretically, more epochs should result in higher accuracy 27 , although a longer runtime was required.…”
Section: Resultsmentioning
confidence: 99%
“…This was supported by the study of Ladds et al 34 , which investigated the classification of animal behavior using a super machine learning model and showed that fewer epochs performed better than more epochs in classifying animal behavior. Furthermore, Fabre et al’s 35 study tested more epochs, but this decreased the moderately vigorous physical activity and increased the percentage error of the accelerometer measurement. More epoch decreasing the performance of a model could be explained by the possibility of overfitting the model.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly including device-measured outcomes will lead to a more comprehensive picture of intervention effectiveness even though other challenges arise from that approach (e.g. comparison of different epoch lengths [ 69 ]). The most promising aspect of device-measured outcomes and accelerometry in particular is the assessment of valid PA and SB data in real-time, resulting in a variety of outcome parameters which have the potential to be easily compared throughout different studies [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a 60 s epoch recording was chosen as this is the recommended way to assess the physical activity levels of children [ 33 , 34 , 35 ]; particularly in longitudinal data collection. However, caution is aired [ 55 ] in the use of a 60 s epoch for future research, due to the misclassification of intensity levels, particularly at vigorous levels, and the potential underestimation of time spent engaging in vigorous physical activity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%